Inverse scattering problem for Sturm–Liouville operators with Bessel singularities on noncompact star-type graphs. (4th November 2015) - Ignatyev, Mikhail
Abstract: In this paper we study the noncompact star-type graph with perturbed radial Schrödinger equation on each ray and matching conditions of some special form at the vertex. The results include the uniqueness theorem and constructive procedure for solution of the inverse scattering problem.